Clinical Outcomes of Patients with Rheumatoid Arthritis Treated in a Disease Management Program: Real-World Results - Santos-Moreno P (Dove Medical Press, 2020)
Pedro Santos-Moreno,1 Paola Castillo,2 Laura Villareal,3 Carlos Pineda,4 Hugo Sandoval,5 Omaira Valencia2 1Scientific Direction, Biomab Center for Rheumatoid Arthritis, Bogotá, D.C., Colombia; 2Research Department, Biomab Center for Rheumatoid Arthritis, Bogotá, D.C., Colombia; 3Medical Direction, Biomab Center for Rheumatoid Arthritis, Bogotá, D.C., Colombia; 4Division of Musculoskeletal and Rheumatic Disorders, Instituto Nacional de Rehabilitación Luis Guillermo Ibarra Ibarra, Mexico City, Mexico; 5Sociomedical Research Unit, Instituto Nacional de Rehabilitación Luis Guillermo Ibarra Ibarra, Mexico City, MexicoCorrespondence: Omaira ValenciaResearch Department, Biomab Center for Rheumatoid Arthritis, Calle 48 #13– 86, Bogotá, D.C., ColombiaEmail o.valencia10@uniandes.edu.coBackground: Care models can affect the clinical outcome of patients with rheumatic and musculoskeletal diseases.Objective: We aimed to compare how an innovative model of a rheumatoid arthritis disease-management program can improve the clinical outcomes of patients compared to a conventional assessment approach.Methods: We performed a retrospective analysis of real-world data from clinical records of a cohort of 5078 patients diagnosed with rheumatoid arthritis who were followed up at the Center of Excellence in Rheumatoid Arthritis vs the clinical outcomes reported in the Colombian National Registry of Rheumatoid Arthritis.Results: We found significant differences in the diagnosis and follow-up between the specialized Center program and the usual care reported by the Colombian National Registry (p< 0.005), including the evaluation of rheumatoid factor, Anti-citrullinated antibodies Disease Activity Score, Health Assessment Questionnaire, number of visits to the rheumatologist, and clinical outcomes measured by the level of disease activity. In addition, when comparing the Center’s clinical outcomes – from baseline to the last follow-up, we found an improvement in the level of disease activity, with patients classified in remission increasing from 20.8% to 58.5% (p< 0.005), and a reduction in those with high disease activity from 18% to 4.7% (p< 0.005).Conclusion: Real-world evidence showed that patients with rheumatoid arthritis who underwent follow-up under an innovative disease-management model improved their clinical outcomes compared with those patients in a conventional assessment program. These results could suggest a way of improving health policies for patients with rheumatoid arthritis.Keywords: disease management, rheumatoid arthritis, quality of life, evidence-based practice, patients